METHODOLOGICAL FOUNDATIONS OF STUDYING THE LIFE AND CREATIVE WORK OF MUQIMIY IN ACADEMIC LYCEUMS - Alimova Manzura Khayrullayevna (International Journal of Literature and Language Studies, 2026)
This article examines the methodological foundations for teaching the life and literary heritage of Muqimiy, one of the prominent representatives of nineteenth-century Uzbek classical literature, in academic lyceums. The study focuses on competency-based education, learner-centered instruction, innovative pedagogical technologies, and interactive teaching methods. Particular attention is given to the application of problem-based learning, project-based learning, Bloom’s taxonomy, case-study methods, digital educational technologies, and formative assessment in developing students’ literary competence, critical thinking, historical awareness, and aesthetic appreciation. Based on theoretical analysis, a methodological model for teaching Muqimiy’s literary heritage is proposed. The findings contribute to improving literature instruction in academic lyceums through contemporary educational approaches while fostering students’ national identity and cultural values.